Adequacy of Sample for Histopathology of Intracranial Lesions Taken from Frame-Based and Frameless Navigation Guided Biopsy - Bhattarai, Sushil Mohan; Khadka, Namrata; Jha, Prabhat; Bista, Pratibha; Jha, Rajiv; Bista, Prakash (Journal of Karnali Academy of Health Sciences, 2022)
Introduction: Neuronavigation-guided biopsy (Frameless and Frame-based stereotactic) is a simplified procedure that helps neurosurgeons to precisely obtain the biopsy of intracranial lesions to establish the complex histopathological diagnosis. The small tissue sample acquired when viewed against the vast heterogeniety of lesions and the rapidly progressive nature of few tumours make the adequacy of sample an important parameter in determining the effectiveness of the procedure, which also has profound financial and disease-related impact on the patients’ life. Methods: A prospective observational study was done in 49 patients who underwent frameless and framebased biopsies at National Neurological Referral Centre, Bir Hospital in one year. The objective of this study was to determine the rate of adequate sample for histopathological examination from intracranial lesions. Results: A total of 36 (73.5%) patients underwent frameless biopsy and 13 (23.5%) patients underwent framebased stereotactic biopsy of intracranial lesions. Overall diagnostic yield was 89.8% with Frameless procedure giving histopathological diagnostic yield of 91.66% and frame-based procedure had diagnostic yield of 84.61%. Hematoma occurred in 2 patients and seizure in one patient. Majority of histopathological diagnosis was glioblastoma (44.9%). Conclusion: Neuronavigation guided biopsy sample of intracranial lesions obtained for histopathological diagnosis is adequate in establishing the final histopathological diagnosis which helps in enhancing patient management and outcome.